ANALISIS PENGARUH UKURAN PERUSAHAAN, LEVERAGE, PROFITABILITAS, EARNINGS PER SHARE, KUALITAS AUDIT, OPINI AUDIT, DAN AUDIT DELAY TERHADAP TIMELINESS ABSOLUT RIIL DAN ABSOLUT SETELAH PENGAUDITAN PUBLIKASI LAPORAN KEUANGAN: Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2011-2013 - Suparlan, SE., M.Sc.A Suparlan (LPPM Universitas Gunung Rinjani, 2019)
The purpose of this study was to investigate the effect of firm size, leverage, profitability, earnings per share, quality audit, audit opinion and audit delay to thetimeliness of absolute real and absolute after the publication of auditing financial statements. This study used 72 companies that reported financial statements have been audited, the selection of the sample using porpusive sampling from 2011 through 2013 all companies listed on the Indonesia Stock Exchange. The results showed that the dependent variable is the real absolute timeliness in which the test statistic F sig 0.000 and 0.475, the adjuated R square regression model 1 is feasible in showing the relationship only between the dependent variable and variable indepednden. And this study shows audit delay affects the real absolute timeliness. This study shows that the absolute timeliness dependent variable after the publication of auditing the financial statements which are statistical test F has sig 0.000 and 0.284, the adjusted R-square regression model 2 is feasible in showing the relationship between the dependent variable and variable indepednden. The results showed profitability and Audit affect the timeliness absolute delay after the publication of auditing financial statements.